Linoleic acid induces human ovarian granulosa cell inflammation and apoptosis through the ER-FOXO1-ROS-NFκB pathway - Zhang, Wenying; Wu, Fuju (Scientific reports, 2024)
Polycystic ovary syndrome (PCOS) is a complex reproductive endocrinological disorder influenced by a combination of genetic and environmental factors. Linoleic acid (LA) is a widely consumed ω-6 polyunsaturated fatty acid, accounting for approximately 80% of daily fatty acid intake. Building upon the prior investigations of our team, which established a connection between LA levels in the follicular fluid and PCOS, this study deeply examined the specific impact of LA using a granulosa cell line. Our findings revealed that LA exerts its influence on granulosa cells (GCs) by binding to the estrogen receptor (ER). Activated ER triggers the transcription of the FOXO1 gene. Reactive oxygen species (ROS)-related oxidative stress (OS) and inflammation occur downstream of LA-induced FOXO1 activation. Increased OS and inflammation ultimately culminate in GC apoptosis. In summary, LA modulates the apoptosis and inflammation phenotypes of GCs through the ER-FOXO1-ROS-NF-κB pathway. Our study provides additional experimental evidence to comprehend the pathophysiology of PCOS and provides novel insights into the dietary management of individuals with PCOS.